Large-scale MIMO MC-CDMA system using combined multiple beamforming and spatial multiplexing - Trung, Nguyen Huu; Binh, Doan Thanh (Vietnam Journal of Science and Technology, 2018)
This paper proposes a novel Large-scale (massive) Multi-input Multi-output Multi-carrier Code division multiple access (LS MIMO ) model and application to Fifth-Generation Mobile Communication Systems (5G). This system uses combined cylindrical array antenna multiple beamforming architecture with spatial multiplexing. The model is optimized by Min-Max criteria in order to minimize side lobes and maximize compression of propagation loss. The Monte Carlo simulation results unify with the analytical solution for system performance.